Perancangan User Experience Aplikasi Mobile Penyewaan Alat Pendakian Gunung menggunakan Pendekatan Human-Centered Design (Studi Kasus : Jawa Timur Outdoor Malang) - Muhammad Alfan Mubarrak; Herman Tolle; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
Climbing equipment rental is a climbing equipment rental service because climbing activities are rarely carried out in a relatively rare period of time and climbing equipment is not cheap. In response to these issues, the mountaineering equipment rental mobile application is designed for convenience in making rentals. This application has a rental by picking up the equipment at the store and rental of equipment by delivery order. The design of this application involves stakeholders who provide mountaineering equipment rental services in the city of Malang, namely Jawa Timur Outdoor Malang. To provide good user experience results, the approach used in designing this application is Human Centered Design because this approach has a broad focus on user needs which involves relevant stakeholders as well as prospective mountaineering equipment rentals who will use this application. The solution design evaluation phase uses usability testing and user experience involving ten participants. The results of usability testing on this application obtained efficacy 100%, efficiency 0.082 goals/second, and user satisfaction 82.3 with an adjective rating of excellent. Furthermore, the user experience test results obtained using the user experience questionnaire (UEQ) get benchmark results by getting very good categories in each aspect, namely attractiveness 2.18, perspicuity 2.13, efficiency 2.20, dependability 2.18, stimulation 2.15, and novelty 1.90.